Self-energy effect and Coulomb potential modulation of the exciton in monolayer MoS2 on polar substrate. (31st October 2017) - Wang, Zi-Wu; Xiao, Yao; Li, Run-Ze; Li, Wei-Ping; Li, Zhi-Qing
Abstract: We theoretically investigate the correction of exciton binding energy in monolayer MoS2 resulting from the exciton couples with surface optical (SO) phonons induced by polar substrate. The total correction of binding energy can be divided into the self-energy effect and modification of Coulomb potential using the unitary transformation method. We find that both the self-energy and Coulomb potential vary from tens of meV to several hundreds of meV depending on the cut-off wave vector of SO phonon modes, polarizability of substrate materials and internal distance between the monolayer MoS2 and polar substrate. An effective Coulomb potential is obtained by combining the modified term into the Coulomb potential. This potentially could be widely used in various two-dimensional materials. Our theoretical results not only propose the ways to externally control the exciton binding energy in experiment, but also enrich the understanding of the exciton properties in the dielectric environment.